Coexistent Types of Atrioventricular Nodal Re-Entrant Tachycardia: Implications for the Tachycardia Circuit - Katritsis, Demosthenes G. (Circ Arrhythm Electrophysiol, 2015)
BACKGROUND—: There is evidence that atypical fast–slow and typical atrioventricular nodal re-entrant tachycardia (AVNRT) do not use the same limb for fast conduction, but no data exist on patients who have presented with both typical and atypical forms of this tachycardia. We compared conduction intervals during typical and atypical AVNRT that occurred in the same patient. METHODS AND RESULTS—: In 20 of 1299 patients with AVNRT, both typical and atypical AVNRT were induced at electrophysiology study by pacing maneuvers and autonomic stimulation or occurred spontaneously. The mean age of the patients was 47.6±10.9 years (range, 32–75 years), and 11 patients (55%) were women. Tachycardia cycle lengths were 368.0±43.1 and 365.8±41.1 ms, and earliest retrograde activation was recorded at the coronary sinus ostium in 60% and 65% of patients with typical and atypical AVNRT, respectively. Thirteen patients (65%) displayed atypical AVNRT with fast–slow characteristics. By comparing conduction intervals during slow–fast and fast–slow AVNRT in the same patient, fast pathway conduction times during the 2 types of AVNRT were calculated. The mean difference between retrograde fast pathway conduction during slow–fast AVNRT and anterograde fast pathway conduction during fast–slow AVNRT was 41.8±39.7 ms and was significantly different when compared with the estimated between-measurement error (P=0.0055). CONCLUSIONS—: Our data provide further evidence that typical slow–fast and atypical fast–slow AVNRT use different anatomic pathways for fast conduction.